Immune microenvironment and immunotherapy for chordoma - Chen, Yujia; Zhang, Hongwei (Frontiers in Oncology, 2024)
Chordoma, as a rare, low-grade malignant tumor that tends to occur in the midline of the body, grows slowly but often severely invades surrounding tissues and bones. Due to the severe invasion and damage to the surrounding tissues, chordoma is difficult to be gross totally resected in surgery, and the progression of the residual tumor is often unavoidable. Besides, the tumor is insensitive to conventional radiotherapy and chemotherapy, thus finding effective treatment methods for chordoma is urgent.Nowadays, immunotherapy has made a series of breakthroughs and shown good therapeutic effects in kinds of tumors, which brings new insights into tumors without effective treatment strategies. With the deepening of research on immunotherapy, some studies focused on the immune microenvironment of chordoma have been published, most of them concentrated on the infiltration of immune cells, the expression of tumorspecific antigen or the immune checkpoint expression. On this basis, a series of immunotherapy studies of chordoma are under way, some of which have shown encouraging results.In this review, we reviewed the research about immune microenvironment and immunotherapy for chordoma, combined with the existing clinical trials data, hoping to clarify the frontiers and limitations of chordoma immune research, and provide reference for follow-up immunotherapy research on chordoma.